2022
DOI: 10.3758/s13423-022-02231-9
|View full text |Cite
|
Sign up to set email alerts
|

The bodily fundament of empathy: The role of action, nonaction-oriented, and interoceptive body representations

Abstract: Mental representations with bodily contents or in various bodily formats have been suggested to play a pivotal role in social cognition, including empathy. However, there is a lack of systematic studies investigating, in the same sample of participants and using an individual differences approach, whether and to what extent the sensorimotor, perceptual, and interoceptive representations of the body could fulfill an explanatory role in the empathic abilities. To address this goal, we carried out two studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
6
1
Order By: Relevance
“…In line with the idea that cognition is embodied, and specifically that mental representations in various bodily formats could play a crucial role in social cognition (Goldman & de Vignemont, 2009), some studies have empirically demonstrated an association between inner and outer bodily processing and social cognition skills, including empathy (Fukushima et al, 2011;Raimo et al, 2023) and ToM (e.g., Shah et al, 2017;Canino et al, 2022). However, despite this recent evidence, results from primary studies are still conflicting, and, for example, other studies point out that a simple relationship between the inner bodily processing, in terms of IAcc, and specific components of empathy and ToM cannot be predicted (e.g., Ainley et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In line with the idea that cognition is embodied, and specifically that mental representations in various bodily formats could play a crucial role in social cognition (Goldman & de Vignemont, 2009), some studies have empirically demonstrated an association between inner and outer bodily processing and social cognition skills, including empathy (Fukushima et al, 2011;Raimo et al, 2023) and ToM (e.g., Shah et al, 2017;Canino et al, 2022). However, despite this recent evidence, results from primary studies are still conflicting, and, for example, other studies point out that a simple relationship between the inner bodily processing, in terms of IAcc, and specific components of empathy and ToM cannot be predicted (e.g., Ainley et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…No association between cognitive/affective empathy and aBR was found. However, it should be underlined that in this review, we did not consider a possible additional component of empathy, that is, action-based or motor empathy (see Blair, 2005), which a study by Raimo et al (2023) suggests being specifically associated with aBR (or body schema).…”
Section: Higher-order Functional Br and Social Cognition Componentsmentioning
confidence: 98%
See 3 more Smart Citations